Electric and Magnetic Response in Dielectric Dark States for Low Loss Subwavelength Optical Meta Atoms. Issue 10 (14th July 2015) - Jain, Aditya; Moitra, Parikshit; Koschny, Thomas; Valentine, Jason; Soukoulis, Costas M.
<x xml:space="preserve">Abstract</x> Artificially created surfaces or metasurfaces, composed of appropriately shaped subwavelength structures, namely, meta‐atoms, control light at subwavelength scales. Historically, metasurfaces have used radiating metallic resonators as subwavelength inclusions. However, while resonant optical metasurfaces made from metal have been sufficiently subwavelength in the propagation direction, they are too lossy for many applications. Metasurfaces made out of radiating dielectric resonators have been proposed to solve the loss problem, but are marginally subwavelength at optical frequencies. Here, subwavelength resonators made out of nonradiating dielectrics are designed. The resonators are decorated with appropriately placed scatterers, resulting in a meta‐atom with an engineered electromagnetic response. As an example, a metasurface that yields an electric response is fabricated, experimentally characterized, and a method to obtain a magnetic response at optical frequencies is theoretically demonstrated. This design methodology paves the way for metasurfaces that are simultaneously subwavelength and low loss.